Clinical Research Authorships: Ethics and Problem-Solving - Katib, Atif (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2020)
The article helps resolve the intricate authorship issue based on global organizations’ regulations. It draws a fine line between authorship and contributorship from the research ethics perspective.